Hexaaminobenzene derived two-dimensional polymer supercapacitor with high specific capacitance and energy density - Wakchaure, Vivek C.; Kottaichamy, Alagar R.; Nidhankar, Aakash D.; Ranjeesh, Kayaramkodath C.; Nazrulla, Mohammed A.; Thotiyl, Musthafa O.; Babu, Sukumaran S. (ACS Applied Energy Materials, 2020)
Recent research interest has been shifted toward energy storage devices, especially supercapacitors, which provide high specific power and long cycle life. In this context, two-dimensional organic polymers are a class of versatile materials found to be useful in energy storage applications. However, the performance is not promising due to the low capacitance, energy density, and cyclic stability. Here, we report a two-dimensional polymer derived from hexaaminobenzene and pyromellitic dianhydride and its excellent supercapacitor performance. The specific capacitance of the two-dimensional polymer is found to be 805 F g(-1) at 0.5 A g(-1) current density in galvanostatic charge-discharge, which is the highest among the organic twodimensional polymer and most of the carbon-based materials. The superior performance of the 2D-polymer compared to a model derivative (350 F g(-1) at 0.5 A g(-1) current density) points to the critical role of a 2D-platform to excel. The high energy density, excellent cyclic stability, and low self-discharge rate support the 2D-polymer supercapacitor as a promising candidate for futuristic applications.
Keywords: 2D-polymer; energy density; Energy storage; hexaaminobenzene; supercapacitor

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting